Metodologi Hindu Nawa Darsana Berdasarkan Paham Filsafat Nyanya - I Ketut Pasek Gunawan (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
Hinduism turns out to have a methodology in obtaining knowledge and truth that is rarely known and understood by Hindus themselves. The methodology turned out to be in Darsana philosophy, especially it can be extracted from the Indian philosophical system known as Sad Darsana which later became known as Nawa Darsana. Nawa Darsana can also be called the nine schools of Indian philosophy from Astika and Nastika, and can also be called the nine methodologies of Hinduism in obtaining truth and knowledge. The Santhi method or positive thinking really needs to be applied to an action in search of knowledge and truth. Furthermore, the last is the Darsanam method or directly realizing that knowledge, namely manifesting what is known and understood from a knowledge so that it will obtain the highest knowledge or the highest truth.